Games people play : the psychology of human relationships - Berne, Eric (Viking, 2010)
"We all play games. In every encounter with other people we are doing so. The nature of these games depends both on the situation and on who we meet. Eric Berne's classic Games People Play is the most accessible and insightful book ever written about the games we play: those patterns of behaviour that reveal hidden feelings and emotions. Wise and witty, it shows the underlying motivations behind our relationships and gives you the keys to unlock the psychology of others - and yourself. You'll become more honest, more effective, and a true team player."--Wheelers.co.nz.